Implementation of Virtual Office Management and Virtual Assistant Applications in Improving the Quality of Learning in Vocational Schools - Winarno Winarno (FALASIFA : Jurnal Studi Keislaman, 2023)
The rapid advancement of technology has revolutionized the field of education, providing new opportunities for enhancing the learning experience. This paper explores the implementation of virtual assistant technology and virtual office management in the context of education to improve teaching and learning processes. Additionally, virtual office management facilitates streamlined document sharing, project collaboration, and group discussions, promoting teamwork and enhancing the overall learning process. This paper investigates various case studies and pilot programs where educational institutions have successfully implemented virtual assistant technology and virtual office management systems. The impact of these technologies on student engagement, academic performance, and administrative efficiency are examined. Knowledge of virtual office management and virtual assistant applications (average value) increase from 4.5 for pre test to 9.5 for post test. The use of virtual assistants in improving the quality of learning from 45% before training to 100% after training. The use of virtual office management in improving the quality of learning from 40 % before training to 90% after training. Furthermore, the challenges faced during implementation and strategies for overcoming them are discussed.